2000
DOI: 10.1111/j.0014-3820.2000.tb00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Androdioecy in the Freshwater Shrimp, Eulimnadia Texana: Estimates of Inbreeding Depression in Two Populations

Abstract: Androdioecy is an uncommon form of reproduction in which males coexist with hermaphrodites. Androdioecy is thought to be difficult to evolve in species that regularly inbreed. The freshwater shrimp Eulimnadia texana has recently been described as both androdioecious and highly selfing and is thus anomalous. Inbreeding depression is one factor that may maintain males in these populations. Here we examine the extent of "late" inbreeding depression (after sexual maturity) in these clam shrimp using two tests: (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 51 publications
4
48
1
Order By: Relevance
“…Consequently, a deep understanding of the role of epigenetic variation in evolution can only be achieved in individuals that are genetically identical but exhibit a range of heritable phenotypes in nature (Heard & Martienssen, 2014 (Costa, 2011;Harrington, 1961;Tatarenkov, Lima, Taylor, & Avise, 2009). In nature, hermaphrodites coexist with a low proportion of males (mostly fewer than 5%) Mackiewicz, Tatarenkov, Taylor, Turner, & Avise, 2006;Mackiewicz, Tatarenkov, Perry, et al, 2006), but no females, which constitutes a rare androdioecious mixed reproductive system Weeks, Crosser, Bennett, Gray, & Zucker, 2000). Given the ability of hermaphrodites to lay unfertilized eggs, outcrossing with males is possible but less frequent than selfing (Mackiewicz, Tatarenkov, Taylor, et al, 2006;Mackiewicz, Tatarenkov, Perry, et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a deep understanding of the role of epigenetic variation in evolution can only be achieved in individuals that are genetically identical but exhibit a range of heritable phenotypes in nature (Heard & Martienssen, 2014 (Costa, 2011;Harrington, 1961;Tatarenkov, Lima, Taylor, & Avise, 2009). In nature, hermaphrodites coexist with a low proportion of males (mostly fewer than 5%) Mackiewicz, Tatarenkov, Taylor, Turner, & Avise, 2006;Mackiewicz, Tatarenkov, Perry, et al, 2006), but no females, which constitutes a rare androdioecious mixed reproductive system Weeks, Crosser, Bennett, Gray, & Zucker, 2000). Given the ability of hermaphrodites to lay unfertilized eggs, outcrossing with males is possible but less frequent than selfing (Mackiewicz, Tatarenkov, Taylor, et al, 2006;Mackiewicz, Tatarenkov, Perry, et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Since that early work, experimental results suggest that sex is more realistically determined by either a large linkage group or possibly by sex chromosomes with limited crossing over (Weeks et al, 1999;Weeks et al, 2000;Weeks et al, 2001). Genetic evidence has revealed that three allozyme loci are physically linked to the sex determining region, and that crossing over among these loci is ~1% (Weeks et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…When we combine our estimates of relative male viability (1 -σ) with previous estimates of inbreeding depression (δ) (Weeks et al 1999(Weeks et al , 2000b, we can begin to address the stability of E. texana's mixed mating system using Otto et al's (1993) model. The estimates of relative male viability reported here were found to range from 0.80 to 0.87 for JT4 and from 0.67 to 0.94 for WAL ( Table 2).…”
Section: Testing Otto Et Al's (1993) Modelmentioning
confidence: 99%
“…The estimates of relative male viability reported here were found to range from 0.80 to 0.87 for JT4 and from 0.67 to 0.94 for WAL ( Table 2). The lifetime cumulative inbreeding depression (δ) in these populations has been estimated as 0.50 for JT4 and 0.68 for WAL (Weeks et al 2000b). Plugging these low (0.80 and 0.67) and high (0.87 and 0.94) estimates of relative male viability for JT4 and WAL, respectively, into Otto et al's (1993) model, we suggest that for the mixed mating systems found in these two populations to be evolutionarily stable, the following conditions must be met: low: α > 1.25β (JT4) and α > 0.96β (WAL) high: α > 1.15β (JT4) and α > 0.68β (WAL)…”
Section: Testing Otto Et Al's (1993) Modelmentioning
confidence: 99%
See 1 more Smart Citation